Experimental Study on Treatment of Glioma by Embyonic Neural Stem Cell Transplnation in Rats - 罗杰 张力 涂汉军 胡钧涛 李新建 李东升 雷霆 (Journal of Huazhong University of Science and Technology. Medical sciences, 2007)
The neural stem cells in Wistar rats were cultured in vitro, purified, and transplanted into C6 glioma model in order to observe their biological characters and provide a basic foundation for treatment of neurological diseases by neural stem cell transplantation. The cells at hippocampal area from gestation 15-day rats were cultured in vitro, and frozen and preserved in liquid nitrogen. C6 tumor-bearing models （n=25） and neural stem cells transplantation models （n=35） were established. When the tumor grew to 3 to 4 weeks, 5 rats in each group were randomly selected for MRI examination. At different intervals, the rats were perfused and sampled for HE staining, GFAP and BrdU immunohistochemical staining. The results showed that after resuscitation of neural stem cells at 1 -4 passages, the cell viability was 40%--63% with the difference being not significant. The cells could proliferate, passage, and most cells transplanted into glioma model survived. The mean survival time in neural stem cell transplantation group and control was 4.28 and 3.88 weeks respectively, and the average tumor size in the former was smaller than in the latter. It was concluded that embryonic neural stem cells in rats could proliferate and differentiate, and after resuscitation the biological characteristic and viability of the cells were not influenced. Neural stem cells had inhibitory effects on the growth of glioma cells and could prolong the survival of rat model.